(untitled) (Research, Society and Development, 2021)
Concrete has advantages such as economy, malleability, durability, resistance, and may have low permeability and maintenance cost. However, the occurrence of cracks is not uncommon, which can occur due to hygrothermal, hygroscopic and other variations. Such cracks are aggravated by the action of weathering agents. In this sense, the present work sought to verify whether the use of ureolytic bacteria, of the type Bacillus subitilis, could correct the cracks through the process of biomineralization and by converting nutrients such as calcium lactate into limestone through the precipitation of calcium carbonate. The sample of Bacillus subitilis was discovered in leachate in a landfill, located in the community of Perema, municipality of Santarém-Pará, Brazil. After the characterization of the sample, temperature resistance test and preparation of the bacteriological solution, the content was applied to fissures of three specimens with fissures of 0.1 mm, 1 mm and 2 mm. After a period of six days, the cracks in the three PCs were completely regenerated, showing the high capacity of Bacillus subitilis in the calcification of the cracks. The results, therefore, proved to be promising, directing the development of new technologies in this field, as well as awakening another look at the environmental issue linked to leachate.